Audiology Students' Clinical Communication During Simulated Peer Role Play Consultations: An Exploratory Study - Kanji, Amisha; Watermeyer, Jennifer; Hassim, Aakifah (American journal of audiology, 2024)
The objectives of this study were to describe the clinical communication practices of student audiologists during case history taking and feedback giving using simulated peer role play consultations and to explore whether clinical communication skills outcomes can be achieved through simulated peer role play. An exploratory, qualitative research design was used for this pilot study. A total of four simulated peer role play consultations were video-recorded, comprising two adult diagnostic audiology case scenarios. Eight online interviews were conducted with the student participants following the simulated audiological consultation. Analysis of the video-recorded sessions incorporated an interactional sociolinguistic focus, and interviews were analyzed using inductive thematic analysis. Findings from the video analysis and interviews were triangulated, with a specific focus on establishing commonalities in terms of communication skills of student clinicians, reflections of their own skills, and the simulated peer patient's reflections on the student clinician's skills. Although variation was noted in terms of case history taking skills, feedback giving was similar among all student clinicians. These communication practices are consistent with findings from related literature on consultations with real patients. Student clinicians reflected on feedback giving as more challenging than case history taking, with room for improvement suggested by the simulated peer patients. Our findings highlight key questions regarding the use of peer simulation in facilitating the development of communication skills for audiological consultations among student audiologists. We discuss some considerations for using this approach to clinical training more effectively. https://doi.org/10.23641/asha.25492804.